FROM MAXIMUM COLLEGE TO THE NATIONAL LIBRARY: USES AND REDEFINITION OF A LIBRARY IN CHILE (1767-1813) - Gutiérrez Ramírez, Eduardo (Revista de Historia Social y de las Mentalidades, 2024)
The following article seeks to track the library that belonged to the Society of Jesus in colonial Santiago, which was extensively used during the presence of the Order in Chile, and after their expulsion would be subject to various policies and actions by the Crown, and then by the first Chilean republican governments. Thus, the library would settle the basis of Chilean culture.